Savings and Loan Behaviour of the Population in the Russian Regions - Gamukin, Valery V. (Economy of Regions, 2020)
The recurrent shocks that accompany the global banking systems are largely due to the savings and loan behaviour of individuals. The study of the ratio of the deposit and credit transactions of individuals for the period 2012 — 2018 in the constituent entities of the Russian Federation allows identifying the features of this behaviour. Considering the regional specificity, the study examines the patterns of changes in the ratio of deposits and loans of the population. Additionally, the study explains the features of such behaviour comparing the change in the ratio of deposits and loans in the regions and the average Russian values. The hypothesis states that there is a stable relationship between these values. The study applies the comparison method as well as the author’s convergence index of the values of the ratio of deposits and loans of the regional population and the average national values. As a result, the behaviour of depositors and borrowers is characterised by numereous features: while the volume of deposits increases in December, January is marked by a withdrawal of funds from banks. As a rule, the decrease in absolute investments is accompanied by the increase in deposits compared to the loans. However, this rule did not work in the acute phase of the crisis of 2014. Consequently, these features result in a proportional dependence of the indicators of loan debts and the volume of deposits. This dependence is close to the ratio “the volume of debt is half the size of the volume of deposits”. The identified relationship is cyclical (close to the sinusoid). Further development of this approach should focus on a deep analysis of factors affecting the savings and loan behaviour in domestic banks. These factors include innate or acquired tendency to save, strength of the response to external pressure, susceptibility to advertising of bank products, inertial decision-making, etc.